2019
DOI: 10.1158/1055-9965.epi-18-1155
|View full text |Cite
|
Sign up to set email alerts
|

Circulating 25-Hydroxyvitamin D Concentration and Risk of Breast, Prostate, and Colorectal Cancers: The Melbourne Collaborative Cohort Study

Abstract: Background: The role of vitamin D in cancer risk remains controversial, and limited data exist on associations between vitamin D and subtypes of specific cancers. We investigated associations between circulating 25-hydroxyvitamin D (25(OH)D) and risk of colorectal, breast, and prostate cancers, including subtypes. Methods: A case-cohort study within the Melbourne Collaborative Cohort Study included 547 colorectal, 634 breast, and 824 prostate cancers, and a sex-stratified random sample of participants (n ¼ 2,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…The highly similar effect of calcitriol on colon tumor and rectal tumor organoids is consistent with the finding that colon and rectal cancers, excluding hypermutated cancers, have similar patterns of genetic alterations [ 65 ]. Moreover, our finding also agrees with the proposed protective effect of vitamin D on both colon and rectal cancers [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The highly similar effect of calcitriol on colon tumor and rectal tumor organoids is consistent with the finding that colon and rectal cancers, excluding hypermutated cancers, have similar patterns of genetic alterations [ 65 ]. Moreover, our finding also agrees with the proposed protective effect of vitamin D on both colon and rectal cancers [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The gut physiology is profoundly affected by the action of vitamin D [ 17 ], and observational studies have established a link between vitamin D deficiency and an elevated risk and poor prognosis of CRC, suggesting that colon and rectal cancer patients might preferentially benefit from an adequate vitamin D status [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Data from recent interventional clinical studies indicate that the addition of vitamin D to standard chemotherapy improves the progression-free survival of metastatic CRC patients [ 29 ]; however, another randomized trial showed no preventive effect on adenoma recurrence [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence over the past decades supports that vitamin D has a beneficial effect on colorectal cancer (CRC) development and outcome [ 1 4 ]. The primary circulating form of vitamin D, 25-hydroxyvitamin D [25(OH) D], is mainly dependent on the exposure to ultraviolet B solar radiation, and levels are therefore depleted during the winter season at high latitudes unless the dietary supplementation is adequate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have identified several risk factors associated with an increased incidence of colorectal cancer including lifestyle factors (eg, obesity, physical inactivity, smoking and heavy alcohol use) and non-modifiable factors (eg, ageing, personal and family history of colorectal cancer or adenoma) 3. Other observational studies conducted in Western countries suggest blood circulating 25-hydroxyvitamin D (25(OH)D) (vitamin D) has a protective role in the development of colorectal cancer 4–8. Some meta-analyses have consistently reported that there was an inverse association between plasma vitamin D concentration in the blood and incidence of, and mortality from, colorectal cancer 9–15…”
Section: Introductionmentioning
confidence: 99%